Gynecological Endocrinology - Calderón Velasco, Rolando (2015)
Actions of insulin in different organs and systems. Androgen physiology in the life of the woman. Prevalence of metabolic syndrome in women. Metabolic syndrome in children and adolescents. Menopause, aging and metabolic syndrome.